The Influence of Celebrity Endorsers and the Advertising Message "Born This Way" on the Brand Image of Skin Game in Purchasing Decisions - Herdiani, Rabeka; Gumelar, Rangga G; Kurniawati, Rd. Nia Kania; Muldi, Ail (Journal of Education Technology Information Social Sciences and Health, 2024)
This research is motivated by the presence of social media which makes it easier for users to access it. Including carrying out promotional and marketing activities. Many companies or brands currently continue to use technology in carrying out modern communications, including the Skin game brand. Researchers want to know about the influence of marketing communications in this case, namely looking at the influence of celebrity endorsers and the message in the "Born This Way" advertisement on the Skin Game brand image in influencing purchasing decisions. The purpose of this research is to determine whether or not there is an influence of celebrity endorsers on the advertising activities that have been carried out. The research method used in this research based on the characteristics of the main research problem is a quantitative method with a sample of 178. The data research method is by questionnaire. All instruments have met the requirements as measurement requirements, because they have been tested so that they have met the requirements for validity testing using product correlation and reliability using Cronbach's alpha, and have passed the prerequisite tests. Data analysis uses the T-test, F-test, and the percentage of influence uses the R Square Adjuster coefficient of determination. The research results show that the significance value of X1 and X2 is 0.000 0.05. So it can be concluded that there is a direct significant influence of X1 and X2 on Y. Then the significance value of X2 is 0.059 0.05. So it can be concluded that there is no direct significant influence of X2 on Z and the significance value of Y is 0.000 0.05. So it can be concluded that there is a significant influence of Y on Z. Based on the analysis of the influence of X1 and X2 through Y on Z, the value of the indirect influence is greater than the value of the direct influence. These results indicate that indirectly X2 through Y has a significant influence on Z.